Wild horses - Stanley, George Edward; Rowe, Michael Langham (New York : Random House, 2007)
Discusses the different wild horses that can be found around the world today, including Chincoteague ponies, Australian Brumbies, American mustangs, and the wild horses of Asia.
"A Stepping Stone book."
Originally published: New York : Golden Books, 2001.
3.6
3-6
Keywords: Wild horses -- Juvenile literature; Wild horses; Horses; Wild horses; Horses